2014
DOI: 10.1007/s10103-013-1509-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the LED phototherapy on femoral bone defects of ovariectomized rats: a Raman spectral study

Abstract: Osteoporosis is a disease characterized by the reduction of bone mineral density. LED wavelengths seem to have similar photo-stimulating effects to laser light. The aim of this study was to assess the Raman shifts: ∼ 960 (phosphate hydroxyapatite), ∼ 1,070 (carbonate hydroxyapatite), and ∼ 1,454 cm (-1) (lipids and proteins) on bone defects of ovariectomized rats treated or not with LED phototherapy (LED-PT). Thirty female rats were divided into four groups (Basal, OVX, OVX+Clot, and OVX+Clot+LED), then subdiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
0
4
0
2
Order By: Relevance
“…6 It has been reported that LED irradiation in the infrared range of the spectrum (from 700 nm to 1 mm wavelength) is able to pass through the dentin barrier 7 and photobiostimulate underlying cells, 8 increasing the cell viability and alkaline phosphatase activity of odontoblast-like cells as well as upregulating collagen type I (Col I) expression. 5,9,10 Additionally, infrared light can improve healing of bone defects mechanically created in rats 11 and reduce pain in temporomandibular disorders. 12 Based on these data, it is reasonable to consider that phototherapy technology with LED represents an interesting alternative for clinical application in restorative dentistry, particularly for stimulation of pulp cells subjacent to the cavity floor.…”
Section: Introductionmentioning
confidence: 99%
“…6 It has been reported that LED irradiation in the infrared range of the spectrum (from 700 nm to 1 mm wavelength) is able to pass through the dentin barrier 7 and photobiostimulate underlying cells, 8 increasing the cell viability and alkaline phosphatase activity of odontoblast-like cells as well as upregulating collagen type I (Col I) expression. 5,9,10 Additionally, infrared light can improve healing of bone defects mechanically created in rats 11 and reduce pain in temporomandibular disorders. 12 Based on these data, it is reasonable to consider that phototherapy technology with LED represents an interesting alternative for clinical application in restorative dentistry, particularly for stimulation of pulp cells subjacent to the cavity floor.…”
Section: Introductionmentioning
confidence: 99%
“…We highlight the laser light used for laser phototherapy (LPT). Over the past 20 years, experimental protocols have been proposed for a considerable number of procedures involving bone repair in animals and humans [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. These protocols are now also used as an aid to an efficient repair of mineralized tissues, as LPT accelerates bone repair by directly affecting, in different ways, the new bone formation.…”
Section: Laser In Dentistrymentioning
confidence: 99%
“…Fibroblast proliferation and its increased activity have been previously detected in individuals and cultures of irradiated cells and are responsible for the high concentration of collagen fibers observed in the irradiated bone. Our previous studies indicate that the effective result of LPT is observed when the treatment is performed in the initial stages of repair, when a large cell proliferation occurs [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Vascular responses to LPT have also been suggested as one of the possible mechanisms responsible for the positive clinical results observed.…”
Section: Laser In Dentistrymentioning
confidence: 99%
See 2 more Smart Citations